Efficient Synthesis of Imidazole-Fused Benzodiazepines Using Palladium-Catalyzed Intramolecular C–N Bond Formation Reaction - Mitra, Sudipta; Darira, Heena; Chattopadhyay, Partha (Synthesis, 2013)
An efficient three-step synthetic route to imidazole-fused benzodiazepines from imidazole-2-carbaldehyde is described. Application of intramolecular Buchwald–Hartwig cycloamination reaction in the final step is shown to be a convenient method for the synthesis of fused seven-membered diazacycles. The reactions proceeded smoothly with both aliphatic and aromatic amines.
Keywords: palladium; catalysis; amination; cyclization; benzodiazepine